Full dimensional quantum scattering study of the H2 + CN reaction# - Bhattacharya, Sayak; Meyer, Hans-Dieter (Journal of chemical sciences, 2012)
Exact wave packet calculations are carried out to investigate the effect of vibrational excitation of the reagent bonds on the dynamics of the CN + H2 → HCN + H process using the multiconfiguration time-dependent Hartree algorithm. The results are compared to the approximate theoretical and the available experimental results. The differences between the results of the theoretical studies are discussed from the point of view of an approximate or exact kinetic energy operator used in the quantum mechanical studies. Deviations between exact theoretical and experimental results points to the inaccuracies of the potential energy surface used. Open image in new window Graphical Abstract Rate constants for the H2 + CN reaction are presented for the reagents in their excited vibrational states by carrying out exact wave packet studies using multiconfiguration time dependent Hartree method.